2019
DOI: 10.1186/s12866-019-1440-8
|View full text |Cite
|
Sign up to set email alerts
|

Lipopeptide mediated biocontrol activity of endophytic Bacillus subtilis against fungal phytopathogens

Abstract: Background The use of chemical fungicides against fungal pathogens adversely affects soil and plant health thereby resulting in overall environmental hazards. Therefore, biological source for obtaining antifungal agents is considered as an environment-friendly alternative for controlling fungal pathogens. Results In this study, seven endophytic bacteria were isolated from sugarcane leaves and screened for its antifungal activity against 10 fungal isolates belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 68 publications
5
59
0
1
Order By: Relevance
“…PCR based screening of AMP gene(s) in the present study clearly reflected the presence srfA, bmyC, and ituD genes in all the endophytic Bacillus strains. These results are in line with other researchers that correlated presence of multiple antifungal peptide genes with antagonistic capabilities of Bacillus strains [20,22,25,26,43,71]. Thus, these AMP genes and their secretions by antagonists act as one of the vital components for effective pathogen inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…PCR based screening of AMP gene(s) in the present study clearly reflected the presence srfA, bmyC, and ituD genes in all the endophytic Bacillus strains. These results are in line with other researchers that correlated presence of multiple antifungal peptide genes with antagonistic capabilities of Bacillus strains [20,22,25,26,43,71]. Thus, these AMP genes and their secretions by antagonists act as one of the vital components for effective pathogen inhibition.…”
Section: Discussionsupporting
confidence: 92%
“…Plant endophytes are reported to suppress plant pathogens and protect plants by multiple mechanisms, for example, antibiosis by producing various antimicrobial metabolites (Backman and Sikora ; Chen et al ). Among these reported metabolites, Bacillus lipopeptides were considered as versatile weapons for plant disease biocontrol, acting as ‘antagonists’ to inhibit the growth of many phytopathogens through their membrane permeabilization, disruption or solubilization (Ongena and Jacques ; Hazarika et al ). Many research have reported the excellent antibiosis of Bacillus lipopeptides, for example, B. amyloliquefaciens PGPBacCA1 was shown to be able to coproduce the lipopeptides surfactin, iturin and fengycin, which were responsible for the effective antifungal effects against S. rolfsii , Sclerotinia sclerotiorum and F. solani (Torres et al ), while surfactin was proved to be responsible for the biocontrol activity of B. subtilis SCB‐1 against diverse fungi including the genera Saccharicola , Cochliobolus , Alternaria and Fusarium (Hazarika et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Shafi et al [201] advocated that the Bacillus species has numbers of antagonizing attributes against plant pathogens including the production of lipopeptides, enzymes, and plant growth promotion. Hazarika et al [202] studied the role of lipopeptides produced by leaf endophytes against 10fungal species.…”
Section: Future Prospects Of Microbial Lipopeptides In Plant Disease mentioning
confidence: 99%